FAKTOR-FAKTOR YANG MEMPENGARUHI FEE AUDIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Wibowo, Afif Imaduddin; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
This research aims to determine the effect of cash holding, managerial structure and company size on audit fee. Furthermore, this research expected to utilized as educational materials and conceptual contributions to widen accounting knowledge, and can be used to compare theoretical knowledge to actual conditions. This research uses a quantitative method. The sample that is used in this research is manufacturing firms that are enlisted on the IDX from the period 2019 to 2021. The total sample used in this research is 237 firms according to the criteria that have been set by the researcher. This research uses the multiple regression method for its data analysis andfound that cash holding and company size are positively affect audit fee, while managerial structure has a negative effect on audit fee.